(untitled) (Research, Society and Development, 2022)
Guttural pouch empyema is usually a consequence of upper respiratory tract infections, especially those caused by Streptococcus equi. In adult horses, empyema is a common disease, whereas considered rare in foals. The aim of this work was to report a case of unilateral guttural pouch empyema in a filly, with a focus on diagnostic and treatment approaches. A 1-month-old filly, 68 kg, Mangalarga Marchador, was admitted because of respiratory distress and enlargement caudally in the head. Clinical examination revealed dyspnea, dysphagia, lymphadenopathy, unilateral enlargement in the retropharyngeal area, and mucopurulent nasal discharge. Further, endoscopic examination confirmed the presence of purulent material inside the left guttural pouch and a diagnosis of empyema was arrived at. Drainage was performed surgically, a catheter was inserted for guttural pouch lavage. The animal received bromexin, dexamethasone, flunixin meglumine, ceftiofur, probiotics, vitamin complexes, and ringer lactate solution. Hematological evaluation performed every 24-72h, showed a decrease in total leukocytes, fibrinogen, platelets, total plasma protein, hematocrit, hemoglobin, and erythrocytes. Eleven days after drainage, the filly’s clinical condition was stable and the wound has healing. The animal was discharged following a good prognosis. Differential diagnoses can include other respiratory diseases, such as guttural pouch timpanism, strangles, and Rhodococcus, which are excluded due to the clinical signs and complementary examinations. In the present case early diagnosis, based on physical examination, hematological parameters, and radiography, combined with adequate treatment methods, including surgical procedures, lavages, antibiotics, and anti-non-steroidal inflammatory therapy, contributed to resolving the guttural pouch empyema in the filly.